2021
DOI: 10.1007/s00134-021-06524-w
|View full text |Cite
|
Sign up to set email alerts
|

External validation of prognostic scores for COVID-19: a multicenter cohort study of patients hospitalized in Greater Paris University Hospitals

Abstract: Purpose The Coronavirus disease 2019 (COVID-19) has led to an unparalleled influx of patients. Prognostic scores could help optimizing healthcare delivery, but most of them have not been comprehensively validated. We aim to externally validate existing prognostic scores for COVID-19. Methods We used “COVID-19 Evidence Alerts” (McMaster University) to retrieve high-quality prognostic scores predicting death or intensive care unit (ICU) transfer from routinely collected d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 49 publications
6
48
0
Order By: Relevance
“…In conclusion, we strongly commend Lombardi et al [ 8 ] for their carefully conducted and comprehensive study. Although prior reports suggest that existing COVID-19 predictive models are at high risk for bias, this study helps lend confidence to a key set of prognostic scores by rigorously evaluating their performance in an independent sample.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…In conclusion, we strongly commend Lombardi et al [ 8 ] for their carefully conducted and comprehensive study. Although prior reports suggest that existing COVID-19 predictive models are at high risk for bias, this study helps lend confidence to a key set of prognostic scores by rigorously evaluating their performance in an independent sample.…”
mentioning
confidence: 78%
“…In this issue of Intensive Care Medicine, Lombardi et al [ 8 ] evaluate the performance of existing prognostic scores to predict in-hospital mortality and the composite outcome of in-hospital mortality or ICU transfer in SARS-CoV-2-infected patients. The external validation was performed in a large database (14,343 patients) containing data collected in 39 hospitals spread across Paris and its surrounding region.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is necessary to use both prognostic risk scores for PE and for COVID-19 mortality to better predict the prognosis in those patients. However as Lombardi Y [17] et al showed that the prognostic scores for COVID-19 were only fairly accurate to predict death in hospitalised COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, while many COVID-19 risk scores have been proposed, almost all have been developed and validated to predict mortality in hospitalized patients. 1 These include the 4C risk score, 2 the ABCS risk score, 3 and the COVID-GRAM risk score. 4 Almost all of these risk scores require laboratory tests and in some cases imaging, which is often unavailable in the outpatient or telehealth settings.…”
Section: Introductionmentioning
confidence: 99%